Domestication and Foreignization Strategy in Translating a Paradise for Travelers - Sama, Gratiana; Kara, Yuliana Maria D'Karmel; Separ, Fransiskus Maria; Watu, Kristina Elvira Fernandes; Mande, Maria Egida Aufa; Jangku, Bonefantura; Supardi, Yuventus; Taba, Yuliana (Universitas Lambung Mangkurat, 2024)
A brochure's message and goal must be taken into consideration when a translator makes a decision. The translator must use both foreignization and domestication as translation method. This study aims to explore the relationship between the foreignization or domestication process and the process of translating cultural terminology from Indonesian into English. In this study, qualitative descriptive methods and discourse analysis were used. Making notes facilitates the classification and identification of the information tourist brochures from Ende Regency of East Nusa Tenggara Province in 2023 are the study's aim. The result showed how the translation procedure influences the strategies used in the translation process. When translating cultural terms, translators mostly used domestication method instead of foreignization.